Seasonal variation of bioactive properties and phenolic composition of Cynara cardunculus var. altilis - Mandim, Filipa (2018)
Cynara cardunculus L. (cardoon) has several health benefits mainly attributed to its abundance in polyphenols. In this study, cardoon heads (capitula) were harvested in Greece during the flowering stage, and the hydroethanolic extracts were assessed in terms of phenolic compounds composition and antioxidant, cytotoxic, anti-inflammatory, and antimicrobial activities. The phenolic profile was evaluated by HPLC-DAD-ESI/MS to better understand the seasonal changes in the individual compound levels and how these changes correlate with bioactive properties. The main phenolic compounds identified were caffeoylquinic and dicaffeoylquinic acid derivatives. Immature heads (Car A: principal growth stage (PGS) 5) had the highest phenolic content (34.3 mg/ g) and cytotoxic (GI50 of 69–268 μg/mL) and anti-inflammatory (IC50 of 183 μg/mL) activities. Sample Car D (PGS 6/7) revealed the highest antioxidant (IC50 of 23–227 μg/mL) and antifungal (MIC of 0.26–0.51 mg/mL) potential. Regarding the antibacterial activity, Car E (PGS 7) revealed the best results (MIC of 0.59–1.18 mg/ mL). This study suggests that the maturity stage of the plant influences the phenolic composition and bioactivity.